2016
DOI: 10.1093/jac/dkw516
|View full text |Cite
|
Sign up to set email alerts
|

Emergence and dissemination of a linezolid-resistantStaphylococcus capitisclone in Europe

Abstract: We identified and characterized an LZR S. capitis clone disseminated in three European countries, harbouring the same multiple resistance and a G2576T mutation in the 23S rRNA. The possible unrecognized wider distribution of this clone, belonging to a species classically regarded as a low-virulence skin colonizer, is of major concern not least because of the increasing use of oxazolidinones.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 25 publications
0
19
0
Order By: Relevance
“…In 2016, Butin et al [17] compared 11 LZR S. capitis with known genome sequences of strains stored in GenBank. All 11 LZR S. capitis strains clustered as a single independent clade, confirming that they belong to a clonal population.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In 2016, Butin et al [17] compared 11 LZR S. capitis with known genome sequences of strains stored in GenBank. All 11 LZR S. capitis strains clustered as a single independent clade, confirming that they belong to a clonal population.…”
Section: Discussionmentioning
confidence: 99%
“…A portion of the extracted genome was subjected to WGS using Illumina technology (HiSeq). Phylogenetic trees were inferred from the WGS data as previously described by Butin et al [17], with some modifications. Briefly, sequences were compared with the seven publicly available S. capitis genomes: CR01 (LN866849), SK14 (ACFR00000000.1), VCU116(AFTX00000000.1), QN1(AJTH00000000.1), AYP1020 (CP007601), C87 (ACRH00000000.1) and LNZR-1 (JGYJ00000000.1).…”
Section: Whole-genome Sequencing (Wgs)mentioning
confidence: 99%
“…Recently, this gene has also been detected in clinical isolates of Enterococcus spp. from North America and Europe ( Brenciani et al, 2016 ; Flamm et al, 2016 ; Cavaco et al, 2017 ; Gawryszewska et al, 2017 ; Pfaller et al, 2017 ), as well as in staphylococci ( Li et al, 2016 ; Butin et al, 2017 ). Phylogenetic analysis has suggested that OptrA belongs to the ABC-F protein subfamily, which is widespread in Gram-positive bacteria ( Murina et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…S. capitis infection has been observed in neonates and adults with infective endocarditis or bone infections and has historically been viewed as susceptible to a broad range of antibiotics [ 1 ]. However, data have suggested the emergence of multidrug-resistant S. capitis in hospitals across Europe [ 23 ]. A recent study also identified S. capitis as a likely causative agent in nosocomial prosthetic joint infections, with multidrug-resistant S. capitis detected in approximately 28% of isolates [ 24 ].…”
Section: Discussionmentioning
confidence: 99%